2005
DOI: 10.1128/iai.73.1.661-665.2005
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Inhibitor of Metalloproteinase 1 Regulates Resistance to Infection

Abstract: Tissue inhibitor of metalloproteinase 1 (TIMP-1)-deficient mice are resistant to Pseudomonas aeruginosa corneal infections. Corneas healed completely in TIMP-1-deficient mice, and infections were cleared faster in TIMP-1-deficient mice than in wild-type littermates. Genetic suppression studies using matrix metalloproteinase (MMP)-deficient mice showed that MMP-9, MMP-3, and MMP-7 but not MMP-2 or MMP-12 are needed for resistance. Increased resistance was also seen during pulmonary infections. These results ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 29 publications
2
41
2
Order By: Relevance
“…To identify which MMP is responsible for the increased resistance, researchers created double null mice by crossing TIMP1 null mice with mice deficient in MMPs known to be inhibited by TIMP1 in vivo, including MMP2, MMP3, MMP7, MMP9, and MMP12. MMP9/TIMP1 double null mice completely lose their resistance to infection, and MMP3/TIMP1 and MMP7/TIMP1 mice have decreased resistance, while MMP2 and MMP12 do not play a role (140). Although these studies did not directly examine the mechanism involved in the protective effect of MMPs in infection with Pseudomonas, other studies have shown that shedding of syndecan1 from airway epithelial cells, which is dependent on cleavage by MMP7, is critical for defense against this organism (169,210).…”
Section: A Evidence For Host Defensementioning
confidence: 78%
“…To identify which MMP is responsible for the increased resistance, researchers created double null mice by crossing TIMP1 null mice with mice deficient in MMPs known to be inhibited by TIMP1 in vivo, including MMP2, MMP3, MMP7, MMP9, and MMP12. MMP9/TIMP1 double null mice completely lose their resistance to infection, and MMP3/TIMP1 and MMP7/TIMP1 mice have decreased resistance, while MMP2 and MMP12 do not play a role (140). Although these studies did not directly examine the mechanism involved in the protective effect of MMPs in infection with Pseudomonas, other studies have shown that shedding of syndecan1 from airway epithelial cells, which is dependent on cleavage by MMP7, is critical for defense against this organism (169,210).…”
Section: A Evidence For Host Defensementioning
confidence: 78%
“…The same MMP can have different roles in different conditions. For example, MMP9 contributes to inflammation in mouse models of stroke, heart attack, Alzheimer's disease, some aspects of asthma and other lung inflammatory conditions, aortic aneurysms and autoimmune encephalomyelitis 9,[106][107][108][109][110] ; however, it functions as an anti-inflammatory agent in models of inflammatory skin and kidney diseases 89,111,112 . Current data indicate that MMP12 contributes to emphysema 113,114 , whereas MMP3 and MMP9 contribute to skin inflammatory conditions 89,115 .…”
Section: Mmps In Human Inflammatory Disease Modelsmentioning
confidence: 99%
“…This protein has been recently described to enhance pathology during infections. For instance, TIMP1-deficient mice are resistant to Pseudomonas aeruginosa corneal infection and show reduced lethality on pulmonary infection with the same microorganism (36). Therefore, the function of timp1 may be important for the elucidation of Analysis of overrepresentation of medical subject heading (MeSH) terms for transcripts corresponding to clusters A-D. A high z-score indicates a significant overrepresentation of a category.…”
Section: Expression Of Ifn-regulated Genes Is Partially Dependent On mentioning
confidence: 99%